Synthesis and characterization of reduced graphene oxide/silica composite for anti-cancer drug delivery system - Okur, Tugba; Gul, Deniz; Sari Yilmaz, Muge (SPRINGER, 2026)
Cancer poses a serious global health problem, responsible for the deaths of millions of people annually. In this context, the design of drug delivery systems has attracted notable interest due to minimizing the adverse effects of cancer drugs on living cells. This study aims to synthesize an efficient carrier for the anticancer agent imatinib mesylate (IM) through the synthesis of a composite material combining mesoporous silica with reduced graphene oxide (rGO@ms) via green synthesis. The release behavior of IM was systematically assessed under different pH conditions (5.0, 6.0 and 7.4) to simulate diverse environments. IM-loaded and unloaded rGO@ms were characterized using UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM) analysis methods. The drug loading capacity of rGO@ms was calculated as 27.79%. Over a 50-h period, IM-loaded rGO@ms was found to have released approximately 80% at pH 5.0, 58% at pH 6.0 and 19% at neutral pH (7.4). The release was significantly higher at pH 5.0, which is attributed to the easier breakdown of the bond between the drug and carrier in an acidic environment. The synthesized composite, which shows favorable release characteristics at lower pH levels, has great potential for cancer treatment. Moreover, the drug release mechanism of the composite was found to closely follow the Korsmeyer-Peppas kinetic model.
Keywords: Reduced graphene oxide; Green synthesis; Mesoporous silica; Composite; Drug delivery; CONTROLLED-RELEASE; NANOPARTICLES; OXIDE; THERAPY; Chemistry; Science & Technology - Other Topics; Materials Science